Knowledge and attitudes of nurses towards pain management at Edward Francis Small Teaching Hospital, Banjul - Tobiloba Oyejide Alex Omotosho; Jainaba Sey-Sawo; Oluwatomilayo Felicity Omotosho; Yahya Njie (Elsevier, 2023)
Background: Pain is known to affect a person's physical, mental health, and quality of life. Therefore, its management and control is a very important goal in patient care. Inability to adequately assess, manage patients' pain and intervene accordingly has an impact on patients' quality of life. Aim: To investigate the knowledge and attitude of nurses towards pain management at the Edward Francis Small Teaching Hospital (EFSTH), in The Gambia. Methods: Descriptive cross-sectional study design was used. A sample of 115 nurses was recruited using the convenience sampling method. Nurses' Knowledge and Attitudes Survey Regarding Pain (NKASRP) was used to assess the knowledge and attitude of pain among nurses. Cronbach's alpha coefficient for this instrument was 0.73. Data were analyzed using the Statistical Package for the Social Sciences software (SPSS, version 20). Descriptive statistics, chi-squared test, and regression analysis were used to analyse the data using SPSS version 20.0. Approval for the study was granted by the EFSTH Research Review Board. Results: One hundred and fifteen nurses filled and returned the questionnaire giving a response rate of 79 %. The mean age of study participants was 29.39 years (SD ± 6.3) and years of working experience was 5.17 years (SD ± 5.0). The mean total score of the NKASRP was 50.0 (SD ± 12.3). The majority of the nurses had inadequate knowledge (60.9 %) and an unfavorable attitude (69.6 %) towards pain management. Logistic regression analysis showed nurses working in the accident & emergency department are more likely to have adequate knowledge (p < 0.05), and BSc degree nurses are more likely to have a favorable attitude towards pain management (p < 0.05). Conclusion: Nurses have inadequate knowledge and unfavorable attitude towards pain management and this continues to be a challenge in health care facilities in The Gambia. Therefore, regular in-service training, extra workshops, and seminars both for students and staff nurses are recommended.